Patient Selection for Drip and Ship Thrombolysis in Acute Ischemic Stroke. Issue 7 (July 2015) - Lyerly, Michael J.; Albright, Karen C.; Boehme, Amelia K.; Shahripour, Reza Bavarsad; Donnelly, John P.; Houston, James T.; Rawal, Pawan V.; Kapoor, Niren; Alvi, Muhammad; Sisson, April; Alexandrov, Anne W.; Alexandrov, Andrei V.
<x xml:space="preserve">Abstract</x> Objectives The drip and ship model is a method used to deliver thrombolysis to acute stroke patients in facilities lacking onsite neurology coverage. We sought to determine whether our drip and ship population differs from patients treated directly at our stroke center (direct presenters). Methods We retrospectively reviewed consecutive patients who received thrombolysis at an outside facility with subsequent transfer to our center between 2009 and 2011. Patients received thrombolysis after telephone consultation with a stroke specialist. We examined demographics, vascular risk factors, laboratory values, and stroke severity in drip and ship patients compared with direct presenters. Results Ninety-six patients were identified who received thrombolysis by drip and ship compared with 212 direct presenters. The two groups did not differ with respect to sex, ethnicity, vascular risk factors, or admission glucose. The odds ratio (OR) of arriving at our hospital as a drip and ship for someone 80 years or older was 0.31 (95% confidence interval [CI] 0.15–0.61, P < 0.001). Only 21% of drip and ship patients were black versus 38% of direct presenters (OR 0.434, 95% CI 0.25–0.76, P = 0.004). Even after stratifying by age (<80 vs ≥80), a smaller proportion of drip and ship patients were black (OR 0.44, 95% CI 0.24–0.81, P = 0.008). Furthermore, we found that fewer black patients with severe strokes arrived by drip and ship (OR 0.33, 95% CI 0.11–0.98, P = 0.0028). Conclusions Our study showed that a smaller proportion of blacks and older adults arrived at our center by the drip and ship model. This may reflect differences in how patients are selected for thrombolysis and transfer to a higher level of care.